DAMPAK PLATFORM MERDEKA MENGAJAR (PMM) TERHADAP KOMPETENSI GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SDN SUDIMARA 6 CILEDUG KOTA TANGERANG - Sela Safitri; Rizki Zuliani; Ina Magdalena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of information technology provides both challenges and opportunities inthe world of education, especially in improving teacher competence to implement the MerdekaCurriculum. This study aims to determine the impact of using the Merdeka Mengajar platform onteacher competence in implementing the Merdeka Curriculum at SDN Sudimara 6 Ciledug,Tangerang City. The research method used is a descriptive qualitative approach with data collectiontechniques through observation, interviews, and documentation studies with teachers, principals,and school operators. Data analysis was conducted systematically with data reduction, datapresentation, and conclusion drawing. The results showed that PMM effectively improved teachers'pedagogical, personality, social, and professional competencies. PMM makes it easy for teachers todesign and implement learning according to Merdeka Curriculum through features such as teachingmodules, self-training, learning communities, and student assessments. In addition, PMMencourages collaboration and creativity between teachers and improves communication withstudents and parents. The obstacles found are the lack of digital literacy of senior teachers andlimited infrastructure such as internet connections and projectors.